Fe(III)-doped coordination polymer of Mn13-clusters with improved activity for oxygen reduction reaction - Schmitt, Wolfgang (My University, 2019)
Fe(III) dopants have been introduced into a porous coordination polymer of Mn13-clusters to form composite materials. The resulting Fe@Mn13-polymer showed enhanced oxygen reduction reaction (ORR) activity, making it a low-cost and noble-metal-free ORR electrocatalyst.
PUBLISHED